2021
DOI: 10.1101/2021.10.23.21265086
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disease waves of SARS-CoV-2 in Iran closely mirror global pandemic trends

Abstract: SARS-CoV-2 genome surveillance projects provide a good measure of transmission and monitor the circulating SARS-CoV-2 variants at regional and global scales. Iran is one of the most affected countries still involved with the virus circulating in at least five significant disease waves, as of September 2021. Complete genome sequencing of 50 viral isolates in an early phase of outbreak in Iran, shed light on the o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Previous genomics analysis in Iran reported six mutations that have a frequency of more than 50% of the sequences, including D614G, P323L, R203K, G204R, F105F, and C241T [28]. In the United States, top mutations were reported as F106F, S76S, L7L, T85I, P323L, D614G, Q57H, L84S, Y541C, P504L, S24L, R203K, and G204R [29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous genomics analysis in Iran reported six mutations that have a frequency of more than 50% of the sequences, including D614G, P323L, R203K, G204R, F105F, and C241T [28]. In the United States, top mutations were reported as F106F, S76S, L7L, T85I, P323L, D614G, Q57H, L84S, Y541C, P504L, S24L, R203K, and G204R [29].…”
Section: Resultsmentioning
confidence: 99%
“…On 03/31/2020, the first spike mutations in D614 were detected in Iran and Figure 7C). Previous study reported that the D614G mutation was first detected in Iran in May 2020 [28]. S477N and S477G strengthen the binding of the SARS-COV-2 spike with the hACE2 receptor [75].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations